2018
DOI: 10.21276/ijcmsr.2018.3.4.15
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Ultrasound in Cutaneous and Subcutaneous Lesions

Abstract: MATERIAL AND METHODS A prospective study of 100 patients in all age groups with skin lesions based on clinical data who presented to Bowring and Lady Curzon Hospital, Victoria Hospital and Vani Vilas hospital attached to Bangalore Medical College and Research Institute, Bengaluru, from November 2014 to May 2015 were subjected to HRUS examination. Study design: It was a Cross sectional study. Totally 100 patients were studied from November 2014 to May 2016. Inclusion criteria: All clinically suspected patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…When spontaneous emission of a two level system was established by Einstein as a necessary mechanism for maintaining thermal equilibrium, it was initially believed to be an irreversible process in which the excited state energy is permanently lost to the infinite bath of available vacuum states . However, the subsequent development of cQED showed that spontaneous emission can be enhanced, suppressed, and even reversibly exchanged with a photonic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…When spontaneous emission of a two level system was established by Einstein as a necessary mechanism for maintaining thermal equilibrium, it was initially believed to be an irreversible process in which the excited state energy is permanently lost to the infinite bath of available vacuum states . However, the subsequent development of cQED showed that spontaneous emission can be enhanced, suppressed, and even reversibly exchanged with a photonic cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Both devices showed malignant melanoma with a spindle-like, fusiform shape. This is one of the typical shapes that is also reported in the literature, [36][37][38][39] one that may be used to distinguish it from other skin lesions. The irregular shape of the metastatic melanoma recorded in the current study has also been noted in the literature.…”
Section: Discussionmentioning
confidence: 61%
“…37 Since such metastases cannot be seen on the surface they present a unique opportunity for the ultrasound to provide diagnostic assessment. 40 In the case of the basal cell carcinoma, several of the recordings showed hyperechoic spots within the lesion (Figures 6 and 8); this feature is noted in the literature as being one of the characteristic signs of BCC, 22,36,37,[39][40][41] which could therefore potentially be used to differentiate the lesion from other lesion types. In addition, since the outline of BCCs is difficult to assess optically, ultrasound may serve as an aid in treatment planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both devices showed melanoma with a spindle-like, fusiform shape. This is one of the typical shapes that is also reported in the literature [ 42 , 43 , 44 , 45 ]: one that may be used to distinguish it from other skin lesions. The irregular shape of the metastatic melanoma recorded in the current study has also been noted in the literature [ 43 ].…”
Section: Discussionmentioning
confidence: 71%